(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2026)
This mixed-methods study investigates teachers’ perceptions of artificial intelligence (AI) tools in English as a Foreign Language (EFL) instruction across three faculties at Fergana State University in Uzbekistan. Drawing on the Technology Acceptance Model (TAM) and contemporary literature on AI in education, the research examines how 67 EFL teachers from the Economy, Science, and English Language and Literature faculties perceive the usefulness, challenges, and integration potential of AI tools such as ChatGPT, Grammarly, and QuillBot. Data were collected through a structured questionnaire (n=67) and semi-structured interviews (n=15). Findings reveal that while teachers across all faculties acknowledge AI tools’ utility for lesson preparation and feedback generation, significant concerns persist regarding academic integrity, student dependency, and assessment validity. Notably, faculty-specific differences emerged: Economy faculty teachers view AI pragmatically as a professional communication aid, Science faculty teachers express cautious optimism about simplifying technical texts, and English Language and Literature faculty teachers demonstrate heightened concerns about preserving authorial voice and critical thinking. The study contributes to understanding AI integration in non-Western higher education contexts and offers practical recommendations for faculty-specific professional development, institutional policy frameworks, and pedagogical adaptation in AI-rich environments.